The relationships between box turtle gut microbiomes and personality - Kaija Harlow; Elizabeth K. Service; Jace E. Geiger; Bradley E. Carlson; Steven J.A. Kimble (PLoS ONE, 2025)
Though well understood in model animals, the microbiome-brain axis has only recently been found to be important in wildlife health. Host behavior is an important component of this axis, and variation in individual animal personalities can shape the dynamics, composition, and evolutionary trajectory of an ecosystem. Relative boldness or shyness is a commonly used personality metric across vertebrate animals, and the composition of an organism’s microbiome may be important in shaping this trait. Turtles have been poorly characterized in terms of behavior and microbiome, though they are the most threatened vertebrate group on Earth and therefore warrant more study. To address this gap, we compared the gut microbiota of bold and shy Eastern Box Turtles to investigate any correlation between microbial composition and personality type. Free-ranging Eastern Box Turtles were captured and assayed for their personality, and cloacal, skin, and oral swab samples were collected. Microbial DNA from swabs was amplified and sequenced. Female turtles had significantly higher alpha microbial diversities than male turtles and shy turtles had a significantly higher microbial diversity than bold turtles. Four significantly overabundant bacteria were found (two in bold turtles and two in shy turtles). The steroid biosynthesis pathway was significantly overrepresented in bold turtles, while the bile acid biosynthesis pathway and purine degradation to urea modules were significantly overrepresented in shy turtles. Firmicutes, Actinobacteria, and Proteobacteria are implicated in the classification of Eastern Box Turtle personality. While our conclusions should be considered in the context of limited sample sizes, our data suggest prominent metabolic pathways, modules, and bacteria that are implicated in different Eastern Box Turtle personality types, suggesting a possible microbial influence on the personality of this well-known but threatened species.